Current situation and future projection of marine renewable energy in China. (26th September 2018) - Hou, Jianchao; Zhu, Xiongwei; Liu, Pingkuo
Summary: The rapid development of China's economy cannot be separated from the massive consumption of fossil fuel. However, potential risks such as the extreme shortage of fossil fuel and the resulting environmental problems are becoming more and more prominent. As a substitution for fossil fuel, renewable energy is playing an increasingly important role in the energy structure adjustment. As a special type of renewable energy, marine renewable energy has been paid much attention by China's government and scientific researchers because of its properties such as cleanness, environmental protection and large reserves. Under the background of energy structure adjustment and electricity market reform in China, the marine renewable energy power market has a bright future. Through querying an amount of literature and information, this paper makes a strategic analysis based on the understanding of the resource endowment, the current industrial status, and policy environment. Then, the PEST‐SWOT strategy analysis model was adopted to analyze the internalities (strengths and weaknesses) and the externalities (opportunities and threats) of the factors affecting the development of marine renewable energy power industry. Then, some countermeasures from the four angles of strategic positioning, institutional arrangement, environmental education, and technical support are proposed to address the weaknesses and threats. Through the research, some conclusions and policy proposals are finally put forward to promote the sustainable development of the industry. Abstract : In this paper, current situation of China's marine renewable energy reserves is investigated. The PEST‐SWOT strategy analysis model is adopted to analyze the internalities (strengths and weaknesses) and the externalities (opportunities and threats) of the factors affecting the development of marine energy power industry. And the corresponding countermeasures and policy suggestions on promoting the sustainable development of the industry are proposed.